OPACITY INFLUENCED INCONSTANT METHOD FOR 3D HOLOGRAPHIC PYRAMID RENDERING - Sarah َQahtan Mohammed Salih; Puteri Suhaiza Sulaiman; Abdul Sattar Arif Khammas; Ramlan Mahmod; Rahmita Wirza O.K. Rahmat (Al-Mustansiriyah Journal of Science)
The rapid growth of computer graphics in human daily life has inspired researchers to maximize image understanding and discover new methods for visualizing 3D objects. However, the image quality is constrained by the depth cue limitations of 3D objects produced by 3D displays. The advent of the holographic hologram pyramid display offers better image quality due to its ability to visualize 3D data with satisfactory depth. In this paper, we present a new visualization method named the “opacity influenced inconstant method” that exploits the custom surface rendering technique to enhance understanding of massive 3D objects for a hologram pyramid display. An algorithm is developed by adding an opacity variable and manipulating the intensity and position of the other variables to enhance the depth cues of a 3D object. The opacity value has the ability to show the inner structure of an object to be visualized if it is available. Our results show significant enhancement on the depth cues of the 3D object that presents as a hologram floating inside a transparent pyramid. The results of a survey conducted on computer graphics students shows that the quality of the hologram was preferred when it was compared to the previous method. In addition, the depth cues of the 3D object were reported to be enhanced by the opacity influenced inconstant method when compared to the previous study and standard shading.